Care plan for prediabetic patients - Marina Nieves Pino Escudero (Fundación para el Desarrollo de la Enfermería, 2013)
Diabetes Mellitus type 2 has a growing impact in the survival and well-being of the population. In recent years its incidence has progressively increased at an alarming rate. However, there are some modifiable risks factors directly related with life styles. Nurse plays a fundamental role in the identification of such factors as well as promoting healthy habits for the prevention of the Diabetes Mellitus type 2.This works presents a standardized care plan for prediabetic state, for this, it had been used the NANDA, NOC, NIC classifications.